Pelatihan Bahan Baku Pangan Halal bagi Pelaku Usaha Mikro dan Kecil di Solo Raya - Sadewa Aziz Diamonda; Purnasari, Nurwulan (Transformatif : Jurnal Pengabdian Masyarakat, 2022)
Knowledge about raw food materials is one of the most critical things to halal that UMKM's business owners must know. Raw food materials that are free from najis will be one of the determinants of the final product's halal status. This program aimed to introduce and provide information about safe raw food materials and non-potentially haram. This program was held to train the food business owner around Solo Raya. They are trained to identify safe raw food materials dan non potentially haram in manufacturing each of their business products.